1987
DOI: 10.1029/jd092id07p08343
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous measurement of stratospheric O3, H2O, CH4, and N2O profiles from infrared limb thermal emissions

Abstract: Thermal emission measurements of the earth's stratospheric limb were made with a cryogenically cooled high‐resolution Michelson interferometer on a balloon flight launched from Palestine, Texas, on November 6, 1984. Infrared spectra for complete limb sequences were obtained over portions of the 700–1940 cm−1 range with an unapodized spectral resolution of 0.03 cm−1 for tangent heights varying from 13 to 39 km. The observed data from 1125 to 1425 cm−1 have been analyzed for simultaneous measurement of O3, H2O, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

1989
1989
1996
1996

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 20 publications
2
4
0
Order By: Relevance
“…This peak is believed to result from extinction by aerosols composed primarily of H2SO 4. Our results are consistent with extinction measurements derived for the same region from analysis of IR stratospheric emission spectra [Abbas et al, 1987].…”
Section: Study Of the Background Levels In The Atmos Spectrasupporting
confidence: 92%
“…This peak is believed to result from extinction by aerosols composed primarily of H2SO 4. Our results are consistent with extinction measurements derived for the same region from analysis of IR stratospheric emission spectra [Abbas et al, 1987].…”
Section: Study Of the Background Levels In The Atmos Spectrasupporting
confidence: 92%
“…et al, 1989]. Since N20 is mixed through showed that when the water lines were weak the corrections to the troposphere[Ablsas et al, 1987], our results, based on the P(7) line were smaller than for the P(8) line and when the column amounts, should agree with the ground level results, and water lines were strong the corrections to the P(7) line were so the disagreement is a measure of the error in our technique. Part large that the line profile might be seriously affected.…”
supporting
confidence: 70%
“…In some countries, the practice of imposing a lower limit on relative humidity of 20% or 35% artificially increases water vapor values. Simultaneous comparisons of balloon-borne in situ methods and remote sensing techniques in the lower stratosphere have produced differences on the order of 100% of the mean value [World Meteorological Organization (WMO), 1986; Abbas et al, 1987a, b].…”
Section: Introductionmentioning
confidence: 99%